BLOB Analysis for Fruit Recognition and Detection - Muhammad Dede Yusuf; RD Kusumanto; Yurni Oktarina; Tresna Dewi; Pola Risma (Universitas Sriwijaya, 2018)
Robot application in agriculture can ease the farming process, especially as the harvesting robot for seasonal fruit that is available in a short time. The addition of